Managing Risks in Financial Market Development : The Role of Sequencing. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper proposes an integrated and risk-based approach to the sequencing and coordination of reforms to develop domestic financial markets. The paper argues that there is a hierarchy of financial markets that reflects the complexity of risks in each market and the interlinkages among markets. On the basis of this hierarchy, a sequencing of market development and risk-mitigation measures is proposed to minimize both macroeconomic and financial risks. Capital account opening can complement (but not substitute for) domestic institutional and market reforms to support the growth of local financial markets. The paper also argues that domestic institutional investors are critical to market development and risk mitigation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet